Topology optimization of structures considering soil-structure interaction. - Cortez, Rômulo Luz (2022)
Topology optimization opens up new perspectives for structural engineering design via optimized layouts. The idea is to find structural layouts with improved performance regardless of the designers experience. As the complexity of boundary conditions increase, new computational methods are required to be developed. One class of unexplored problems concerns the design of structures resting on elastic soil instead of rigid supports. In that context, this master by research project proposes and investigates the topology optimization method applied to soil-structure interaction problems. In this scheme, the soil and the structure are modeled separately with the Indirect Boundary Element Method (IBEM) and with the Finite Element Method (FEM), respectively. The response of the structure interacting with the soil is obtained by imposing continuity and equilibrium conditions at their interface. The Topology Optimization of Binary Structures (TOBS) method is chosen to solve the structural stiffness maximization problem subject to a volume constraint. Numerical results show that the effects of the soil-structure iteration are relevant when designing a structure via topological optimization for different structure-soil stiffness ratios. Furthermore, the results show that the presence of voids in the soil alters its flexibility, regardless of the constitutive properties of the soil and that this significantly alters the optimized structure.